Respostas

A melhor resposta!
2014-07-09T19:49:37-03:00
A) (x + 3) (x + 4)                               x = - 7 + - 0 / 2     
x² + 4x + 3x + 12                             x´ e x'' = - 7 + 0 / 2 = - 7 / 2
x³ + 7x + 12 = 0
Delta = 7² - 4.1.12
Delta = 49 - 48
Delta = 1


b) (a - 2) (a - 7)                              x = 9 + - √25 / 2 
a² - 7a - 2a + 14                             x = 9 + - 5 / 2
a² - 9a + 14 = 0
Delta = (- 9)² - 4.1.14                      x' = 9 + 5 / 2 = 14 / 2 = 7
Delta = 81 - 56                               x'' = 9 - 5 / 2 = 4 / 2 = 2
Delta = 25                                   


c)  (y - 6) (y + 6)
y² + 6y - 6y - 36
y² - 36 = 0
y² = 36
y = + - √36
y = + - 6

d) (2x - 5) (3x - 2)                            x = 19 + - √121 / 12
6x² - 4x - 15x + 10                          x = 19 + - 11 / 12
6x² - 19x + 10 = 0
Delta = ( - 19)² - 4.6.10                    x' = 19 + 11 / 12 = 30 / 12 = 5 / 2
Delta = 361 - 240                            x'' = 19 - 11 / 12 = 8 / 12 = 2 / 3
Delta = 121

e) (1 - 2x) (4 + 3x)                           x = - 5 + - √121 / 12
4 + 3x - 8x - 6x²                              x = - 5 + - 11 / 12
4 - 5x - 6x² .(- 1)
- 4 + 5x + 6x² = 0                            x' = - 5 + 11 / 12 = 6 / 12 = 1 / 2
6x² + 5x - 4 = 0                               x'' = - 5 - 11 / 12 = - 16 / 12 = - 4 / 3
Delta = 5² - 4.6.(- 4)
Delta = 25 + 96
Delta = 121

f) (- x + 4) (x + 5)                              x = 1 + - √81 / - 2
- x² - 5x + 4x + 20                             x = 1 + - 9 / - 2
- x² - x + 20 = 0 
Delta = ( - 1)² - 4.(- 1).20                    x ' = 1 + 9 / - 2 = 10 / - 2 = - 5
Delta = 1 + 80                                   x'' = 1 - 9 / - 2 = - 8 / - 2 = 4
Delta = 81

g) (x² + 3x) (x - 4)                              x = 1 + - √49 / 2 
x³ - 4x² + 3x² - 12x                             x = 1 + - 7 / 2
x³ - x² - 12x = 0
Delta = (- 1)² - 4.1.(- 12)                     x¹ = 1 + 7 / 2 = 8 / 2 = 4
Delta = 1 + 48                                   x'' = 1 - 7 / 2 = - 6 / 2 = - 3
Delta = 49

h) (x³+³+¹+3) (x³+³+¹-3)

i) (1-4³+¹) (1+1³+¹)

Não entendi o que vc fez na H e na I.
1 5 1